MicroRNAs Constitute a Negative Feedback Loop in Streptococcus pneumoniae–Induced Macrophage Activation. (16th March 2016) - Griss, Kathrin; Bertrams, Wilhelm; Sittka-Stark, Alexandra; Seidel, Kerstin; Stielow, Christina; Hippenstiel, Stefan; Suttorp, Norbert; Eberhardt, Martin; Wilhelm, Jochen; Vera, Julio; Schmeck, Bernd
Abstract: Streptococcus pneumoniae causes high mortality as a major pneumonia-inducing pathogen. In pneumonia, control of innate immunity is necessary to prevent organ damage. We assessed the role of microRNAs (miRNAs) as regulators in pneumococcal infection of human macrophages. Exposure of primary blood-derived human macrophages with pneumococci resulted in transcriptional changes in several gene clusters and a significant deregulation of 10 microRNAs. Computational network analysis retrieved miRNA-146a as one putatively important regulator of pneumococci-induced host cell activation. Its induction depended on bacterial structural integrity and was completely inhibited by blocking Toll-like receptor 2 (TLR-2) or depleting its mediator MyD88. Furthermore, induction of miRNA-146a release did not require the autocrine feedback of interleukin 1β and tumor necrosis factor α released from infected macrophages, and it repressed the TLR-2 downstream mediators IRAK-1 and TRAF-6, as well as the inflammatory factors cyclooxygenase 2 and interleukin 1β. In summary, pneumococci recognition induces a negative feedback loop, preventing excessive inflammation via miR-146a and potentially other miRNAs.